Characteristics and treatment patterns of autism spectrum disorder in China, 2020. (November 2022) - Luo, Yanan; Zhao, Yanan; Wang, Yiran; Liang, Richard; Hong, Chenlu; Yang, Yingkai; Zheng, Xiaoying
Highlights: The treatment patterns of ASDs among Chinese children is currently unknown. This study is the first to report empirical results of the characteristics and treatment patterns of ASD, based on a nationwide autism investigation covering the largest sample of ASD cases in China. We found a higher proportion of autistic children in families with highly educated parents, advanced parental age at childbirth, and a family history of mental disorders or intellectual disorders. Higher odds of non-treatment were found among children who were male and had ASD diagnosed later on. Abstract: This study aimed to investigate the characteristics of children diagnosed with ASD in China and to estimate ASD treatment patterns in 2020. This study used data from the 2020 Survey on Family Circumstance and Demand Support and Resources among Autistic Children in China. The study sample included 4, 557 children diagnosed with ASD aged 2–16 years old. Data were collected through questionnaires completed by parents. Of the 4, 557 children with ASD, there was a male-to-female ratio of 5.75:1, and the average age when ASD risk symptoms were first reported was 27.97(SD=10.83) months. Higher proportions of families with highly educated parents (college and above; around 58%) and advanced parental age at childbirth (≥35 years; over 50%) were found among autistic children. Additionally, about 41.05% of autistic children had an immediate family member diagnosed with mental/intellectual disorders. In terms of the treatment patterns for autistic children, 84.82% had received behavioral and developmental treatments and 77.74% had received therapy-based treatments, whereas 3% children had not received any treatment. Higher odds of non-treatment were found among children who were male (OR=1.69, 95% CI: 1.01, 3.03) and had ASD diagnosed later on (OR= 1.02, 95% CI:1.01, 1.03), as compared to their counterparts. Future studies will need to explore the etiology of the disparities of ASD, and policy efforts are critically needed to understand and address the barriers for children with ASD to receive appropriate treatments.